Synthesis of a small library of copper activated NNSN molecules for the treatment of bacterial infections and cancer - Eschliman, Kayla Michelle Jamison (Kansas State University, 2021)
Bacterial infections are a serious health issue worldwide and the number of cases is anticipated to continue rising. The problem is especially dire when considering the increase in resistant bacteria that are becoming ever more difficult to treat. On average, someone gets an antibiotic-resistant infection every 11 seconds and every 15 seconds someone dies, according to the Centers for Disease Control and Prevention Antibiotic Resistance Threats Report 2019. Cancer is also a severe health problem, ending nearly 9 million lives worldwide each year. Copper activated drugs are of growing interest due to their ability to be used for anti-bacterial and anti-cancer applications. NNSN molecules are a novel, patented class of drugs displaying an extended thiourea motif. These drugs are synthesized by coupling a pyrazole ring and phenyl isothiocyanate together. Derivatives are produced by the various substituents added to either the pyrazole or the phenyl isothiocyanate and the placement of these substituents on the aromatic ring. The current library of NNSN compounds contains 134 derivatives. A structure activity relationship study on these compounds has been conducted to determine the best possible structures to treat Staphylococcus aureus infections. Despite not having any stereocenters, these small molecule drugs exhibit copper-activated reactivity toward bacterial infections (including S. aureus (Gram-positive), Escherichia Coli (Gram negative)), and Mycobacterium tuberculosis, and cancerous murine cell lines (Melanoma (B16F10), Glioblastoma (GL26), and Pancreatic Cancer (Pan02 and KPC)). NNSNs are non-toxic until activated by copper, the necessary concentration of which only exists naturally in the biological environment at the site of infection or within a tumor microenvironment. Copper (I/II) is an endogenous metal that is limited in the human body because of its ability to create reactive oxygen species, which are extremely damaging to bodily tissues. This presents a unique opportunity for selective activity, making the probability of harmful side effects significantly lowered. This mode of action is a theory that is strengthened by evidence determined using multiple computer modeling studies and by the calculation of copper binding constants using ultraviolet visible spectroscopy on a gradient of solutions.
Keywords: Copper; Activation; Cancer; Bacterial; Infection; Synthesis